2019
DOI: 10.1080/17512786.2019.1625719
|View full text |Cite
|
Sign up to set email alerts
|

If Only They Knew: Audience Expectations and Actual Sourcing Practices in Online Journalism

Abstract: This article answers the question "Are the sourcing practices in Finnish online journalism trustworthy?" Here, trustworthiness is operationalized as the fulfillment of audience expectations towards sourcing practices. To this end, expectations of young Finnish adults (aged 18-28) were compared to the observed practices of Finnish online journalists. A total of 36 news items (from 12 journalists working in three newsrooms, published in 2013 and 2017) were analyzed. The analysis indicates that online journalists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Overall, the influence of transparency strategies on trustworthiness should, as underlined by experimental studies (e.g. Kruikemeier & Lecheler, 2018) and surveys (Manninen, 2020), therefore be questioned. This is in line with other studies showing little or no effects of such strategies to increase trustworthiness on the audience's existing attitudes regarding news media (Curry & Stroud, 2019;Karlsson, Clerwall, & Nord, 2017;Karlsson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the influence of transparency strategies on trustworthiness should, as underlined by experimental studies (e.g. Kruikemeier & Lecheler, 2018) and surveys (Manninen, 2020), therefore be questioned. This is in line with other studies showing little or no effects of such strategies to increase trustworthiness on the audience's existing attitudes regarding news media (Curry & Stroud, 2019;Karlsson, Clerwall, & Nord, 2017;Karlsson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies confirm that young audiences are aware of and appreciate news that meets established quality standards. A study from Finland shows that young adults wish for even more investigation, verification of journalistic content, and credible sources (Manninen 2019). Drok and Hermans (2015) confirmed these findings for the Netherlands and highlighted the importance of location- and time-independent availability.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Further it has been concluded that young consumers are educated and enjoy news that fulfills certain quality requirements. According to a Finnish research, young individuals want greater inquiry, confirmation of media content, and trustworthy sources ( Manninen, 2020 ). Since younger folks value news in their daily lives, but do not always absorb it actively, making them “a population that is of tremendous interest to news producers throughout the world, and one which they are finding more difficult to reach” ( Schwaiger et al, 2022 ).…”
Section: Theoretical and Hypothesis Supportmentioning
confidence: 99%